Smart cities and Sustainable Development Goals – Barriers in the process to sustainable public procurement - Camargo, Matheus Alexandre da Silva; Cortese, Tatiana Tucunduva Philippi; Vils, Leonardo (Revista Nacional de Gerenciamento de Cidades, 2020)
A literature review on the barriers that hinder the implementation of sustainable public procurement (SPP) in different environments. Smart cities are not just technological cities, they must also be sustainable and value the optimization of resources, so that it is possible to ensure sustainable production and consumption patterns. This article aims to contribute to the survey of future research on the topic. Sustainable public procurement is part of the Sustainable Development Goals (SDGs), specifically SDG 12 - Sustainable Consumption and Production, in addition to the fact that it is one of the goals of the United Nations. Therefore, the implementation of SPP by governments throughout the world is necessary, standardized specifically according to the legislation of each country. Results indicate that there are several barriers aligned to SPP, often recurring for both public managers and suppliers. However, in the recent years, several countries have been adapting to the new agenda.